What would it take? Enhancing outcomes for high-ability students with disability - Townend, Geraldine; McGregor, Marie; Alonzo, Dennis; Nguyen, Hoa T. M. (Frontiers in Education, 2024)
A troubling misconception exists that high-ability is enough to ensure positive educational, mental health and well-being outcomes for gifted students. Of course, we want all our students to develop their potential in school, so why are so many of our more able children failing in school and enduring the repercussions of reduced well-being? The notion that a student is not highly able if they are receiving poor grades is a common societal misconception, and this is commonly the case for gifted learners with disability, also known as twice-exceptional students. A considerable number of school students globally have intellectual ability in the gifted range, a high number of those are gifted with co-occurring disability, and many remain unidentified. It is, therefore, likely that a significant percentage of our classrooms have students who may be flying under the radar and are likely to be underachieving or unsupported within the school system. The purpose of this article is to highlight the issues around gifted students with disability that may contribute to their underachievement. Also discussed is how educators, counsellors and other key stakeholders can support this unique population of students.